2015
DOI: 10.2174/1573397111666150522094821
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Pathogens are Likely to be Responsible for the Development of Ankylosing Spondylitis

Abstract: The role of oral bacteria in the etiology of ankylosing spondylitis (AS) is examined in this review. Periodontitis is related to AS to a significant degree, and periodontitis is significantly more prevalent in patients with AS. Anti-Pophyromonas gingivalis and anti-Prevotella intermedia antibodies titers are higher in AS patients than in healthy subjects. Eight randomized controlled trials that used sulfasalazine were reviewed. Moxifloxacin and rifamycin are significantly effective in the treatment of AS. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…It has also been reported that periodontitis is linked to AS, and patients with AS are more likely to suffer periodontitis [9]. Comparing AS patients with healthy people, AS patients have the higher level of anti- Pophyromonas gingivalis [10], again suggesting potential interaction between some specific microbiota with AS.…”
Section: Evidence Of As-microbiome Interactionsmentioning
confidence: 98%
“…It has also been reported that periodontitis is linked to AS, and patients with AS are more likely to suffer periodontitis [9]. Comparing AS patients with healthy people, AS patients have the higher level of anti- Pophyromonas gingivalis [10], again suggesting potential interaction between some specific microbiota with AS.…”
Section: Evidence Of As-microbiome Interactionsmentioning
confidence: 98%
“…Oral microbiota (with over 700 species being harbored in the oral cavity) have a role in periodontal disease and in turn, play a contribitory role in periodontitis [44]. Comparing AS patients with healthy people, AS patients have the higher level of anti-Pophyromonas gingivalis, suggesting potential interaction between some specific microbiota and AS [45][46][47][48]. Martinez et al suggested infection was closely related with patients with SpA.…”
Section: Ankylosing Spondylitis (As)mentioning
confidence: 99%
“…Indeed, oral bacterial DNA and antibodies to P. gingivalis, T. forsythia and P. intermedia have been demonstrated in synovial fluid and the site of inflammation in rheumatoid arthritis [64]. It is also interesting that the medications with an antibacterial action against these species (including levofloxacin and clarithromycin) seem to have a beneficial effect in RA [65].…”
Section: Oral Microbiome In Rheumatoid Arthritismentioning
confidence: 99%